Policy Implementation in the Education Sector: A Case Study of Free Tuition Policy in South Tangerang City - Sa’adih, Sa’adih; Hutauruk, Rosinta Paulina; Putri, Maryam Pratiwi (Universitas Sang Bumi Ruwa Jurai, 2022)
This study examines the implementation of the free tuition policy (Program Pendidikan Gratis) in South Tangerang City, focusing on how policy objectives are translated into practice at the school and local government levels. Using a qualitative case study approach, the research explores the roles of key actors, policy communication, resources, and institutional support. Findings indicate that while the policy is generally well-received by the community, challenges remain in budget adequacy, school autonomy, and clarity of operational guidelines. The study contributes to a deeper understanding of education policy implementation dynamics in urban Indonesia.